Supervisory Boards and Corporate Social Responsibility Disclosure: A Meta-Analysis - DAMAYANTI, Cacik Rut (2024)
By synthesizing quantitative research results in 39 studies on how corporate governance mechanisms impact Corporate Social Responsibility (CSR) activities, this study conducts a Hunter-Schmidt meta-analysis to investigate the role of the Supervisory Board (SB) on the effectiveness of CSR activities. This study examines the role of the board independence, non-executive directors, and outside directors in CSR performance, which measured by environmental policy, and corporate social performance. Using JASP software, this study found that based on the previous studies in the quantitative approach, the independence board and the non-executive director influence the CSR disclosure positively and significantly. In contrast, earlier studies found that the outside director had a contradictory result. This meta-analysis offers a notable outcome in that the high quality of the publication provides evidence related to the relationship between SB's CSR activities, and the monitoring system provides adequate supervision to encourage the executive to concern the stakeholders and shareholders more equally.